SEPARATION OF MECHANICAL VENTILATION - Parbawa Kusuma, Ida Bagus Wisnu; Kuning Atmajaya, I Nengah (E-Jurnal Medika Udayana, 2014)
The weaning from mechanical ventilation can be defined as the process of letting the ventilator either directly or in stages. Indication of weaning from mechanical ventilation, seen from several parameters such as disease processes, PaO2, PEEP, FiO2, pH, Hb, awareness, body temperature, cardiac function, lung function, drugs sedative agent or paralysis agent, and psicologic status of patient. Based on the length of the weaning, can be devided into two, long-term weaning dan short-term weaning. Short-term weaning, such as T-Piece, CPAP, SIMV, and PSV. Long-term weaning, such as T-Piece and Intermitten Mandatory Ventilation. There are two that affect the length of weaning, such as nonventilator factor and ventilator factor. Nonventilator factor such as sedation drug abuse, malnutision, lack of psychological support, and lack of support if there is damage to the left ventricle. Ventilator factor such as over ventilation and under ventilation. Factor that lead to failure in weaning affected by respiratory control center, respiratory muscle strength, and load on the respiratory muscles.
Keywords: mechanical ventilation, weaning from mechanical ventilation